Willingness to Pay for Social Health Insurance and Its Predictors among Government Employees in Mujja Town, Ethiopia - Feleku Mekonnen Degie; Yeshambel Agumas Ambelie; Yared Mulu Gelaw; Getahun Fentaw Mulaw; Fentaw Wassie Feleke (The Scientific World Journal)
Background. Social health insurance is one of the possible organizational mechanisms for raising and pooling funds to finance health services, private health insurance, community insurance, and others. Objective. The study was aimed to assess willingness to pay for social health insurance and associated factors among government employees in Mujja town, Ethiopia. Methods. An institutional-based cross-sectional study was conducted on the total sample size of 375 study respondents. A simple random sampling technique was employed. Data were entered into EPI info 7 and analyzed by Statistical Package for Social Sciences version 22.0. Multivariable logistic regression was used to identify independent predictors by controlling confounding variables. Statistical significance was declared at p<0.05. Results. This study revealed that 37.6% (95% CI: 33.1%, 42.61%) respondents were willing to pay for social health insurance. In the final model, respondents who ever heard about health insurance schemes were seven times (AOR = 7.205; 95% CI: 1.385, 37.475) more likely willing to pay for social health insurance. Thos who had history of difficulty and having other source to cover medical bills were 92.6% (AOR = 0.074; 95% CI: 0.009, 0.612) and 94.6% (AOR = 0.054; 95% CI: 0.011, 0.257) less likely to pay, respectively. Conclusions. Willingness to pay for social health insurance was low. Being heard about health insurance, history of difficulty, and having other sources to cover medical bills were associated factors. Thus, it is recommended that media promotion and these factors should be considered for the successful implementation of the scheme.